IMPLEMENTASI USER CENTERED DESIGN DALAM PENGEMBANGAN WEBSITE MANAJEMEN DATA SENTRA HAK KEKAYAAN INTELEKTUAL POLITEKNIK NEGERI SIRIWIJAYA - Malahayati; Rika Sadariawati; Ebtaria Nadeak; Sri Rahayu Rezeki; Lenno Nardo; M Irfan Apriansyah (LPPM Universitas Abdurrab, 2026)
Intellectual Property Rights (IPR) play a strategic role in supporting innovation and productivity in higher education institutions. However, IPR management at Politeknik Negeri Sriwijaya (POLSRI) is still conducted manually, leading to various issues such as delays in the submission process, low data accuracy, and difficulties in tracking and reporting. This study aims to design and develop an integrated web-based IPR management information system by applying the User-Centered Design (UCD) approach. The research employs a prototype development method combined with UCD principles, encompassing literature review, observation, interviews, requirements analysis, interface design using Figma, system development using the Laravel framework, and usability evaluation through the System Usability Scale (SUS). The results indicate that the developed Sentral HKI (SHKI) system effectively facilitates digital submission, validation, status tracking, archiving, and reporting of IPR data in accordance with the needs of users, including lecturers, students, and administrative staff. Usability evaluation demonstrates that the system achieves a good level of ease of use and meets user requirements. Therefore, the SHKI system is considered effective in improving efficiency, accuracy, and transparency in IPR data management at POLSRI and has the potential to support sustainable institutional IPR governance.